Pengaruh Gerakan Pan-Islamisme Jamaluddin Al-Afghani terhadap Semangat Juang Umat Islam di Berbagai Negara - Arifatul Khiyaroh; Muhammad Imam Syafi; Chusnul Mutia; Ahmad Fikri Mujtahid; Desty Endah; Abid Nurhuda (Program Pascasarjana UNU Surakarta, 2023)
Pan-Islamism is commonly known asnationalism is a movement pioneered by Jamaluddin al-Afghani, a reformer from Afghanistan. This movement aims for Muslims to unite and fight together to fight colonialism from the West. The movement spread to various countries which at that time were experiencing setbacks in the hope that this Pan-Islamism political movement could have an influence on the rise and independence of Muslims to become more advanced. So the purpose of this study is to describe the influence of the Pan-Islamism al-Afghani movement in several countries on the fighting spirit of Muslims. Method used is a library by collecting primary and secondary data then grouped and analyzed systematically so that conclusions can be drawn. The results of the research show that the influence of the Pan-Islamism movement carried out by al-Afghani is able to bring Muslims to a better direction, and his thoughts spread to various countries ranging from India, Afghanistan, Paris, Egypt, Turkey to Indonesia.